CREATION AND MANAGEMENT OF A REAL ESTATE CADASTRAL INFORMATION BASE - Abdiraxmatov Nuriddin Abdiraxmatovich; Mirzayev Jonibek Oltiyevich; Hamdamova Dildora Murodulla qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation. This paper analyzes the process of creating an information resource for real estate cadastre, its importance and effectiveness. The real estate cadastre is an important information base for the protection of property rights, property management and the calculation of state taxes. The paper examines the application of modern technologies for collecting, storing, updating and using cadastral information, including geographic information systems (GITS) and digital platforms. It also analyzes the problems that arise in the process of creating and managing information resources, and ways to solve them. As a result, the possibilities of ensuring legality in the real estate sector, developing the real estate market, and improving the quality of public administration through the formation of an effective cadastral information system are determined.